The Effects of Anesthetics on the Cortex—Lessons From Event-Related Potentials - Baron Shahaf, Dana; Hare, Gregory M. T.; Shahaf, Goded (Frontiers in Systems Neuroscience, 2020)
Consciousness under general anesthesia is a dreadful condition. Various EEG-based technologies were developed, on the basis of empirical evidence, in order to identify this condition. However, certain electrophysiological phenomena, which seem strongly related with depth of anesthesia in some drugs, appear less consistent with other anesthetic drugs. There is a gap between the complexity of the phenomenon of consciousness and its behavioral manifestations on one hand, and the empirical nature of the reported electrophysiological markers, which are associated with it, on the other hand. In-fact, such a gap might prevent us from progressing toward unified electrophysiological markers of consciousness under anesthesia, which are applicable to all anesthetic drugs. We believe there is a need to bridge this conceptual gap. Therefore, in this work we will try to present a theoretical framework for such bridging. First, we suggest focussing on neuropsychological processes, which seem to have a clear role in the behavioral manifestations of consciousness under anesthesia, but seem, nevertheless, better defined than consciousness itself – such as perception and attention. Then, we suggest analyzing the effects of anesthesia upon these neuropsychological processes, as they are manifested in the EEG signal. Specifically, we will focus on the effects of anesthesia upon event related potentials (ERP), which seem more easily associable with neuropsychological modeling.